Implementasi seni dan budaya Toraja berbasis web menggunakan framework codeigniter 4.3.1 (studi kasus: seni dan budaya Toraja): Web-based implementation of Toraja arts and culture using codeigniter framework 4.3.1 (case study: Toraja arts and culture) - Sety Ratte; Julius Panda Putra Naibaho (Universitas Papua, 2023)
Sety Rante Rerung, D3 Department of Computer Engineering, Faculty of Engineering, University of Papua, April 2023, web-based implementation of Toraja arts and culture using the CodeIgniter 4.3.1 framework (case study: Toraja arts and culture). Supervised by Julius P.P. Naibaho, S.Kom., M.Kom. Toraja art and culture are customs that continue to be passed down from generation to generation, both for generations in Toraja land and Toraja people who leave Toraja land to migrate, to maintain the heritage of art and culture, knowledge about art and culture should continue. preserved by utilizing current technological developments, one of which is the website. Based on the problem of maintaining and preserving Toraja art and culture so that it remains preserved by utilizing current technology, namely websites, the author provides a solution by creating a website to implement Toraja art and culture using the CodeIgniter 4.3.1 framework. With this website, it is hoped that it can help maintain information and preserve Toraja art and culture, both for people living in Toraja and people who have left Toraja to migrate.